Object-relations in maltreated and abused children assessed with the Rorschach inkblots and the Mutuality of Autonomy Scale (Urist) - Rivera Carpio, Sylvia (2001)
The objective of the study was to observe the quality of the object-relations in maltreated and institutionalized boys and girls, assessed with the Rorschach inkblots and the Mutuality of AutonomyScale (MOA) of Urist. The participants were 23 children of both sexes, aged 8 to 10,who had been maltreated in their household and were institutionalized in an orphanage. The results showed that both tools reflect object-relations well. There are significant differences, depending on the sex, time of Separation from their maternal figure and the type of maltreatment they received. Furthermore, the children represent more adaptative, conventional and positive object relations what is related with their resources.